Use of antimicrobials in patients with COVID-19 without prior evaluation of an associated bacterial infection (Research, Society and Development, 2021)
This paper aims to clarify and present discussions about the COVID-19 disease, its variants and prevention measures, as well as clarifying the excessive use of antimicrobials in the protocols of patients infected with it, as this practice can intensify an already existing public health problem, which is antimicrobial resistance. The methodology used in this research was a literature review on bacterial resistance due to the indiscriminate use of antimicrobials and the possible impacts caused in the COVID-19 pandemic, as well as the variants of worldwide concern, based on the Scientific Electronic Library Online databases - SCIELO, National Library of Medicine - PubMed, CAPES Journal Portal, Academic Google and National Health Surveillance Agency (ANVISA). Based on the literature presented here, it is concluded that COVID-19 is a disease caused by the acute respiratory syndrome (SARS-CoV-2) presenting a clinical spectrum ranging from asymptomatic infections to severe conditions. Several variants have emerged in several countries modifying the dynamics of transmissibility and potential immune flight from the disease, the Delta variant (B.1.617.2) being a greater threat to public health due to its high transmissibility. The misuse and excessive use of antimicrobials prescribed for the treatment of this disease can favor the emergence of superbugs and such resistance is a global problem. Therefore, the help of laboratory and clinical tests is essential to carry out a therapeutic intervention, observing the best options for each clinical case, since COVID-19 is a new disease and still under study.